2010
DOI: 10.1002/eqe.978
|View full text |Cite
|
Sign up to set email alerts
|

Simplified inelastic seismic analysis of base‐isolated structures using the N2 method

Abstract: In the paper a simplified nonlinear method has been applied to the analysis of base-isolated structures. In the first part, a three-linear idealization of the capacity curve is proposed. The initial stiffness is defined based on the first yielding point in the superstructure, whereas the secondary slope depends on the failure mechanism of the superstructure. A consequence is a much more pronounced secondary slope, which does not correspond to the presumptions used in the originally proposed N2 method. A parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…In the extended N2 method the results of the pushover analysis are further multiplied by correction factors, which can be obtained by means of elastic modal analysis for a given distance from the CM. Recently the N2 method has been applied, though with some modifications, to baseisolated symmetric (27) and asymmetric structures (11). In pushover analyses the lateral loads were always applied in the vertical plane through the centre of mass (CM) of the superstructure.…”
Section: Seismic Analysesmentioning
confidence: 99%
“…In the extended N2 method the results of the pushover analysis are further multiplied by correction factors, which can be obtained by means of elastic modal analysis for a given distance from the CM. Recently the N2 method has been applied, though with some modifications, to baseisolated symmetric (27) and asymmetric structures (11). In pushover analyses the lateral loads were always applied in the vertical plane through the centre of mass (CM) of the superstructure.…”
Section: Seismic Analysesmentioning
confidence: 99%
“…In the authors' recent paper [14], several modifications of the original N2 method were proposed, to account better for the behavior of base-isolated structures. The major modifications are a threelinear idealization of the pushover (capacity) curve, based on the first yield of the superstructure, and the introduction of an additional damping reduction factor, which should, in general, be obtained by an iterative procedure, and represents the reduction in demand due to the damping of the isolators.…”
Section: Symmetric Building Structuresmentioning
confidence: 99%
“…It was found that, even under such complex irregularity conditions, the results obtained by using this approach correlated well with the results obtained from NLDA. In order to merge the proposed N2 method for base-isolated structures [14] with the extended N2 method for fixed-base structures, several issues have to be first addressed:…”
Section: Plan-asymmetric Building Structuresmentioning
confidence: 99%
See 2 more Smart Citations